UNDERGRADUATE IMPLANT DENTISTRY TRAINING IN SAUDI DENTAL SCHOOLS - AlKindi, Mohammed; Ramalingam, Sundar; Almunif, Meshal; Abuhaimed, Abdullateif; Alkharan, Hassan (Journal of Ayub Medical College Abbottabad, 2018)
Background: Implant dentistry training at the undergraduate level has been introduced only recently in Saudi dental schools and there is only limited data available about it. The objective of the present study was to evaluate the current status of undergraduate dental implant education in Saudi Dental Schools. Methods: A two-part questionnaire-based study was conducted in Saudi university dental schools targeted towards undergraduate program directors to assess the quantity and quality of implant dentistry training being integrated into the curriculum. In addition, interns were asked to assess the degree of exposure and their satisfaction regarding implant dentistry education. Results: Five program directors (83.3%) and 195 interns (82.9%) responded to the questionnaires. Implant dentistry was taught to the undergraduate students in multidisciplinary departments with teaching hours ranging from 22-30 hours. Only three schools exposed students to laboratory (workshop) or clinical training. There was agreement among the program directors in respect of the didactic contents. Majority of the interns reportedly acquired knowledge regarding implant dentistry based on theoretical (96.1%), laboratory (33.5%) and/or clinical (30%) training. While 50% of the interns agreed to acquiring knowledge by assisting and observing dental implant procedures, only 52.8% of the interns expressed satisfaction regarding implant dentistry training obtained during their undergraduate period. Conclusion: The present study revealed variability in undergraduate implant dentistry training offered at Saudi dental schools. In order to optimize this and to produce competent dentists, learning guidelines for such courses should be developed and implemented by competent authorities. Background: Implant dentistry training at the undergraduate level has been introduced only recently in Saudi dental schools and there is only limited data available about it. The objective of the present study was to evaluate the current status of undergraduate dental implant education in Saudi Dental Schools. Methods: A two-part questionnaire-based study was conducted in Saudi university dental schools targeted towards undergraduate program directors to assess the quantity and quality of implant dentistry training being integrated into the curriculum. In addition, interns were asked to assess the degree of exposure and their satisfaction regarding implant dentistry education. Results: Five program directors (83.3%) and 195 interns (82.9%) responded to the questionnaires. Implant dentistry was taught to the undergraduate students in multidisciplinary departments with teaching hours ranging from 22-30 hours. Only three schools exposed students to laboratory (workshop) or clinical training. There was agreement among the program directors in respect of the didactic contents. Majority of the interns reportedly acquired knowledge regarding implant dentistry based on theoretical (96.1%), laboratory (33.5%) and/or clinical (30%) training. While 50% of the interns agreed to acquiring knowledge by assisting and observing dental implant procedures, only 52.8% of the interns expressed satisfaction regarding implant dentistry training obtained during their undergraduate period. Conclusion: The present study revealed variability in undergraduate implant dentistry training offered at Saudi dental schools. In order to optimize this and to produce competent dentists, learning guidelines for such courses should be developed and implemented by competent authorities. Key words: Implant dentistry; Dental implants; Dental education; Undergraduate dentistry